Solving Quality and Reliability Optimization Problems for MEMS with Degradation Data - Lundia, Yash; Jain, Kunal; Krishna, Mamanduru Vamsee; Tiwari, Manoj Kumar; Raj, Baldev (Materials and Failures in MEMS and NEMS, 2015)
This chapter contains sections titled: Abbreviations Introduction Notations and Assumptions Reliability Model Numerical Example Conclusions